2020
DOI: 10.1016/j.gendis.2020.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the early diagnosis of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most prevalent cancers globally. In contrast to the declining death rates observed for all other common cancers such as breast, lung, and prostate cancers, the death rates for HCC continue to increase by ~2–3% per year because HCC is frequently diagnosed late and there is no curative therapy for an advanced HCC. The early diagnosis of HCC is truly a big challenge. Over the past years, the early diagnosis of HCC has relied on surveillance with ultrasonography (US) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
195
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(196 citation statements)
references
References 170 publications
(182 reference statements)
1
195
0
Order By: Relevance
“…The pooled AUROC curve was 0.94 (95%CI: 0.91-0.95) [102] . In the future, the combination of different imaging modalities and non-invasive biomarkers are likely to improve the ability of early HCC detection [103] .…”
Section: Early Detection Of Hccmentioning
confidence: 99%
“…The pooled AUROC curve was 0.94 (95%CI: 0.91-0.95) [102] . In the future, the combination of different imaging modalities and non-invasive biomarkers are likely to improve the ability of early HCC detection [103] .…”
Section: Early Detection Of Hccmentioning
confidence: 99%
“…However, AFP alone is not enough for HCC diagnosis, screening or surveillance [4]. Its suboptimal performance, that is, increased levels in benign liver pathologies and teratomas or low levels in small HCC [5], has prompted that US and European guidelines allow HCC surveillance with or without AFP control, in contrast to Asian guidelines that recommend its use in combination with imaging techniques or even other biomarkers [2]. Nonetheless, it remains as a supplemental test when only low-quality or inconclusive images are available.…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated the diagnostic e ciency of CCT7 using independent datasets in the GEO and TCGA database. The ROC curve analysis showed that CCT7 has a higher AUC value than AFP, the current golden biomarker of diagnosis for HCC [44,45]. In addition, the positive predictive value of CCT7 was better than AFP.…”
Section: Discussionmentioning
confidence: 96%